Acculturation and Capital Punishment: The Effect of Mexico Versus United States Cultural Orientations on Public Support for the Death Penalty - Updegrove, Alexander H. (International journal of offender therapy and comparative criminology, 2019)
Few studies have explored how the intersection of vastly different cultures, like those of the United States and Mexico, influences death penalty support. The present study uses the Acculturation Rating Scale for Mexican Americans-II to examine whether individuals who are more closely aligned with U.S. culture are more likely to support the death penalty than individuals more closely aligned with Mexican culture. Findings support this conclusion. Findings also reveal that the significance of predictors for death penalty support varies between Mexican- and U.S.-oriented subsamples. Thus, this study reaffirms the importance for researchers to consider cultural context when examining public attitudes toward the death penalty, especially when using samples from a single, multicultural country such as the United States.